Distal Insertional Footprint of the Brachialis Muscle: 3D Morphometric Study. (10th November 2015) - Kamineni, Srinath; Bachoura, Abdo; Behrens, William; Kamineni, Ellora; Deane, Andrew
Abstract : Objective . The purpose of this study is to describe the three-dimensional morphometry of the brachialis muscle at its distal attachment to the ulna. Methods . Fifty cadaveric elbows were dissected and the brachialis distal insertion was isolated on the ulna bone and probed with a three-dimensional digitizer, to create a three-dimensional model of the footprint. Measurements and analysis of each footprint shape were recorded and compared based on gender and size. Results . There was significant gender difference in the surface length (P = 0.002 ) and projected length (P = 0.001 ) of the brachialis footprint. The shapes of the footprint also differed among the specimens. Conclusion . The shape of the brachialis muscle insertion differed among all the specimens without significant variation in gender or sides. There was also a significant difference in muscle length between males and females with little difference in the width and surface area. Significance . The information obtained from this study is important for kinematic understanding and surgical procedures around the elbow joint as well as the understanding of the natural age related anatomy of the brachialis footprint morphology.